The key role of the scaffold on the efficiency of dendrimer nanodrugs - Caminade, Anne-Marie; Fruchon, Séverine; Turrin, Cédric-Olivier; Poupot, Mary; Ouali, Armelle; Maraval, Alexandrine; Garzoni, Matteo; Maly, Marek; Furer, Victor; Kovalenko, Valeri; Majoral, Jean-Pierre; Pavan, Giovanni M; et al. (Nature communications, 2015)
Dendrimers are well-defined macromolecules whose highly branched structure is reminiscent of many natural structures, such as trees, dendritic cells, neurons or the networks of kidneys and lungs. Nature has privileged such branched structures for increasing the efficiency of exchanges with the external medium; thus, the whole structure is of pivotal importance for these natural networks. On the contrary, it is generally believed that the properties of dendrimers are essentially related to their terminal groups, and that the internal structure plays the minor role of an 'innocent' scaffold. Here we show that such an assertion is misleading, using convergent information from biological data (human monocytes activation) and all-atom molecular dynamics simulations on seven families of dendrimers (13 compounds) that we have synthesized, possessing identical terminal groups, but different internal structures. This work demonstrates that the scaffold of nanodrugs strongly influences their properties, somewhat reminiscent of the backbone of proteins.
Keywords: Molecular Dynamics Simulation; silany; biokompatibilní materiály; průtoková cytometrie; aza sloučeniny; Aza Compounds; Nanoparticles; Diphosphonates; Molecular Structure; lidé; bisfosfonáty; simulace molekulární dynamiky; Flow Cytometry; monocyty; nanočástice; Bone Density Conservation Agents; polylysin; molekulární struktura; Biocompatible Materials; Monocytes; Silanes; Polypropylenes; inhibitory kostní resorpce; polypropyleny; Polylysine; dendrimery; Dendrimers; Humans